PNGM-1, a novel subclass B3 metallo-β-lactamase from a deep-sea sediment metagenome. (September 2018) - Park, Kwang Seung; Kim, Tae Yeong; Kim, Ji Hwan; Lee, Jung Hun; Jeon, Jeong Ho; Karim, Asad Mustafa; Malik, Sumera Kausar; Lee, Sang Hee
Highlights: The metallo-β-lactamase (MBL) PNGM-1 has been identified from a deep-sea sediment metagenome. PNGM-1 is a novel subclass B3 MBL that pre-dates the antibiotic era. PNGM-1 hydrolysed almost all β-lactams. Abstract: Objectives: In order to find antimicrobial resistance gene(s) pre-dating the use of antibiotics through metagenomics, functional screening of a metagenomic library from the deep-seep sediments of Edison Seamount (ca. 10 000 years old) was performed. Methods: Among 60 antimicrobial-resistant clones, a single clone with the highest minimum inhibitory concentration (MIC) for ampicillin was selected. Sequence analysis revealed a new metallo-β-lactamase (MBL) gene, designated as bla PNGM-1 . PNGM-1 retains a zinc ion-binding motif (H116 XH118 XD120 H121, H196 and H263 ), conserved in subclass B3 MBLs. The catalytic parameters of purified PNGM-1 and the MICs of β-lactams for Escherichia coli TOP10 transformants harbouring the bla PNGM-1 gene were assessed. Results: Antimicrobial susceptibility testing indicated reduced susceptibility to penicillins, narrow- and extended-spectrum cephalosporins, and carbapenems in E. coli TOP10 transformants harbouring the bla PNGM-1 gene. In addition, kinetic analyses revealed that PNGM-1 hydrolysed almost all β-lactams. Conclusions: The PNGM-1 enzyme is the first case of a subclass B3 MBL derived from a functional metagenomic library of a deep-sea sediment that pre-dates the antibiotic era.